PENGARUH KOMPETENSI, PENEMPATAN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI SEKRETARIAT JENDERAL KEMENTERIAN LUAR NEGERI - Ahrul Tsani F. (MIX: JURNAL ILMIAH MANAJEMEN, 2013)
Abstract: The research was conducted to analyze how strong is the effect ofcompetency, work placement and motivation on performance of the employees of theSecretariat General of Ministry of Foreign Affairs. Phenomenon indicated thatperformance achievement of the Ministry showed by the result of LAKIP appraisal onlymeet the CC criteria. This could be linked to the low performance of the Ministry staff,affected by competency, work placement and motivation factors. The design of theresearch is causal design which aimed to measure how strong are the effect ofcompetency, work placement and motivation on performance. The measurement of thevariables is using Likert scale and data were collected through questionnaire to 186respondents. The data obtained was analyzed using SPSS. The results of multipleregression analysis and t-test proved that the competency had no effect, while workplacement and motivation significantly effected on performance. In conclusion, theresearch showed that the process of work placement by considering academicachievement and motivation from a good relationship with superiors could effect to theachievement of the employees performance.Keywords: competency, work placement, motivation, performance